Contextual Meanings Of Qur'ānic Near-Synonyms And Their Translations - Abdul-Qader Khaleel Abdul-Ghafour; Ashinida Aladdin; Intan Safinaz Zainudin; Norsimah Mat Awal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study identifies the contextual meanings of some selected Qur'ānic near-synonyms and the semantic differences that exist between them, as explained in the Holy Qur'ān. It also elucidates how the semantic differences between the selected Qur'ānic pairs are reflected in the English translations. Three pairs of Qur’anic near-synonyms are chosen for this study. The collected data are qualitatively analyzed based on the RC-S approach by Murphy. The findings show that some semantic differences exist between the selected pairs of Qur'ānic near-synonyms, and some semantic differences are not reflected in the English translations. An example of the investigated Qur’anic near-synonyms is the pair of جوع and مسغبة (hunger). The findings reveal that مسغبة (famine) denotes extreme and severe hunger of a large number of people. It is also associated with weakness, fatigue, exhaustion, and thirst. However, its near-synonymجوع (hunger) is more general and does not have the same semantic features asمسغبة (famine). It is shown that translating both words by Arberry as ‘hunger’ is inappropriate since the semantic differences between them are not reflected in the English translation. This study presents recommendations that could be useful for translators, readers, and interested researchers.